2018
DOI: 10.13057/biodiv/d190424
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of nekton in the upstream of Wampu Watershed, North Sumatra, Indonesia

Abstract: Desrita, Muhtadi A, Tamba IS, Ariyanti J, Sibagariang RD. 2018. Community structure of nekton in the upstream of WampuWatershed, North Sumatra, Indonesia. Biodiversitas 19: 1366-1374. River is a habitat for many aquatic organisms. Water quality is themain river characteristic that strongly influences distribution pattern, biodiversity, and abundance of aquatic organisms. Nekton isaquatic organism that swims and moves actively on their desire, for example, fish, shrimp, amphibian and also big aquatic insects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 13 publications
0
18
0
3
Order By: Relevance
“…Small sampling location (not spread evenly) and one-time sampling might have caused the low diversity found in that study. As a comparison, studies in Wampu watershed by Muhtadi et al (2017) and Desrita et al (2018) found at least 26 species of fish, 3 freshwater shrimps, and 1 freshwater crab. The objective of this study was to provide basic data on diversity of aquatic organisms in North Sumatra, Indonesia.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Small sampling location (not spread evenly) and one-time sampling might have caused the low diversity found in that study. As a comparison, studies in Wampu watershed by Muhtadi et al (2017) and Desrita et al (2018) found at least 26 species of fish, 3 freshwater shrimps, and 1 freshwater crab. The objective of this study was to provide basic data on diversity of aquatic organisms in North Sumatra, Indonesia.…”
Section: Introductionmentioning
confidence: 94%
“…Pranata et al (2016) found 3 orders, 7 families of 13 genera and 16 species of fish in Sangkir River, Rokan Hulu Regency, Riau Province. Muhtadi et al (2017) and Desrita et al (2018) found 12 species and 3 species of Bagridae in the upstream waters of Batangtoru watershed with a total of 37 species of nekton species.…”
Section: Abundance and Species Composition Of Nektonmentioning
confidence: 99%
See 1 more Smart Citation
“…In the eastern part (point 4) and the river (point 11), the proportions between species are uneven, with lower species richness (4-8 species) due to lower diversity. Desrita et al (2018Desrita et al ( , 2020 stated that the diversity index is not only based on species richness but influenced by the respective proportions of species in the community. The high diversity of crustaceans at stations 6 and 8 is also accompanied by a high evenness index close to 1 and the absence of a dominant one (C value <0.25).…”
Section: Diversiy Indexmentioning
confidence: 99%
“…When the water level rises, Yellow finned barb will move to lower waters to breed. Yellow finned barb fish are benthopelagic fish that live in schools in the morning [17,4,5,6]. The distribution of Yellow finned barb fish is from large rivers, then tributaries to floodplains, especially during the rainy season.…”
Section: Introductionmentioning
confidence: 99%